Escape from Warsaw - Serraillier, Ian. (New York : Scholastic, 1972)
The story of three Polish children and their experience in Europe during World War II.
Formerly: The silver sword.
Keywords: World War, 1939-1945 -- Juvenile literature; World War, 1939-1945 -- Children; Children's literature